Pedagogic Mapping of Teacher Competence in Inclusive Schools - *, Gunarhadi; *, Sunardi; Andayani, TriRejeki; Anwar, Moh (Proceeding of International Conference on Teacher Training and Education, 2016)
The rapid movement of inclusive education has changed the demand of competence in inclusive schools. Thisresearch was a survey on mapping teachersâ pedagogic competence on educational service for children withspecial needs in inclusive schools.Â  This research aims to (1) to identify the degree of teachersâ knowledge oneducational services for children with special needs, (2) to measure the degree teachersâ skill on teachingchildren with special needs in inclusive schools. This research involved 50 teachers in elementary schoolsimplementing inclusive education in the District of Solo Raya, Central Java Indonesia. The data was collectedby means of questionnaire and interview. The data was, then, analyzed by descriptive quantitative andqualitative. The research indicated the result that (1) the teachers in inclusive schools had inadequateknowledge on instruction for children with special needs, (2) they had limited skill on teaching children withspecial needs. The research concluded that most teachers in regular schools had limited knowledge and skills.In addition to the lack of experience in teaching children with special needs, most teachers were noteducationally qualified in special education. It is recommended that the education authority facilitates thepotential of teachers through trainings so as to improve the educational service for children included ininclusive schools.